PERTIMBANGAN PEMANGKU ADAT PETALANGAN DALAM PEMBATALAN HIBAH TANAH DI DESA SEGATI KECAMATAN LANGGAM KABUPATEN PELALAWAN - Suarsanti, Devi; Ismi, Hayatul; Hasanah, Ulfia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Land grants in customary land law are a free agreement on land granting. To prove land grants according to customary law that are still recognized, at the time of registration of rights to land grants systematically as proof of customary land rights. Land rights are not an agreement whose implementation must be fulfilled by submitting juridical rights to the party receiving the grant, but rather legal actions that cause the transfer of ownership rights to the land concerned to those who are given a grant. But in essence, a grant that has been granted cannot be withdrawn either in customary law or in the Civil Code. The purpose of this thesis is: First, to find out the consideration of the stakeholders of the traditional petalangan in the cancellation of the village land grant from Segati, the sub-district of Pelalawan District. Secondly, to find out the efforts made by indigenous people towards the cancellation of land grants carried out by the traditional petalangan stakeholders in the village, the sub-district of Pelalawan district. This type of research can be classified as sociological, sociological or empirical legal research consisting of identification of law (unwritten) and research on legal effectiveness. In this study the author directly conducts research on the location or place under study in order to provide a complete and clear picture of the problem under study. This research was conducted in Segati Subdistrict Village, Pelalawan Regency, while the population and samples were all parties related to the problems examined in this study, data sources used primary data, secondary data, and tertiary data, data collection techniques in this study with observation, interview, and literature study. From the results of the study two things can be concluded. First, what is considered by the stakeholders in the cancellation of the land grant is; because the land is not used as it should / is not managed, the object of the grant that is in dispute, and is not approved by all indigenous stakeholders. Secondly, the efforts made by indigenous peoples towards the canceled land grant by conducting deliberations with traditional stakeholders as grant providers, and by resolving disputes with the PT. Nusa Wana Raya. Suggestion of the author First, based on the considerations made by the adat stakeholders in the cancellation of the land grant, in this case the customary petalangan institution must make a writtenJOM Fakultas Hukum Universitas Riau Volume VI Edisi 1 Januari- Juni 2019 2regulation related to the cancellation of the grant. Second, regarding the efforts made by indigenous peoples to the cancellation of the land grant, indigenous peoples also need to understand the importance of registering customary land with national law to the national land agency